Induksi Embriogenesis Somatik Pada Anggrek Vanda Sumatrana Schltr. dengan Penambahan Beberapa Konsentrasi Asam 2,4-Diklorofenoksiasetat (2,4-D) - Anita Tri Astuti; Zozy Aneloi Noli; Suwirmen Suwirmen (Jurnal Biologi Universitas Andalas, 2019)
The research about induction of somatic embryogenesis of  Orchid Vanda sumatrana Schltr.  by giving 2,4-Diclorophenoxiacetic acid (2,4-D), was conducted from May to July 2016 in plant Physiology and tissue Culture Laboratory, Biology Departement, Matematics and Natural Science Faculty, Andalas University. The aim of this study was found the concentration of 2,4-D to induce somatic embryogenesis of Vanda sumatrana. The research used Completely Randomized Resign (CDR) with 6 treatments and 4 replication. The treatments were : without 2,4-D (control); 1 mg/L; 2 mg/L; 3 mg/L; 4 mg/L; 5 mg/L. The result showed that 2 mg/L 2,4-D and 3 mg/L 2,4-D were concentrations to induct somatic embryogenesis.